Current Methods of Dietotherapy of Cow's Milk Protein Allergy in Infants - Leyla S. Namazova-Baranova; Elena A. Vishneva; Daria S. Chemakina; Gennady A. Novik; Mikhail A. Tkachenko; Lilia R. Selimzyanova; Anna A. Alexeeva; Yuliya G. Levina; Kamilla E. Efendieva; Vera G. Kalugina; Elena A. Dobrynina (Union of pediatricians of Russia, 2021)
Nowadays there is progressive increase in the number of patients with allergy around the world. It was revealed that microbiome composition changes at early age correlate with the frequency of atopic diseases development. Various clinical studies have shown that variety of factors (even from prenatal development) influence microbiota composition. Children with atopic diseases have certain features of microflora development that can precede the disease debut. Cow's milk protein is one of the major allergens in the first year of life. Such sensitization may be present in children on both formula and breastfeeding, however it is not the indication for its interruption. In cases when breastfeeding is not possible, we should use specialized therapeutic formulas in children with cow's milk protein allergy. The use of the "Nutrilon Amino acids Syneo" formula effectively eliminates allergy symptoms and improves the gut microbiota composition in young children. Moreover, its use additionally reduce the frequency of infectious diseases and the use of antibacterial drugs.